Farewell to the priestly writing? : The current state of the debate - Hartenstein, Friedhelm, 1960-; Schmid, Konrad, 1965- (Ancient Israel and its literature, 2019)
In discussions of the origin of the Pentateuch, the Priestly source traditionally constitutes an undisputed reference point for different source-critical models, and it is the only literary layer with concise terminology and a theological conception that can be extracted from a non-Priestly context. This English translation of Abschied von der Priesterschrift? Zum Stand der Pentateuchdebatte revisits the scholarly debate surrounding the Documentary Hypothesis and the so-called Priestly material's position either as an independent written source or as a redaction within the books of Genesis through Deuteronomy. Contributors include Christoph Berner, Erhard Blum, Jan Christian Gertz, Christoph Levin, Eckart Otto, Christophe Nihan, and Thomas Römer.